1996
DOI: 10.1021/bi951988q
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Enzyme Thermostability Observed in the Molecular Structure ofThermusaquaticusd-Glyceraldehyde-3-phosphate Dehydrogenase at 2.5 Å Resolution,

Abstract: The crystal structure of holo D-glyceraldehyde-3-phosphate dehydrogenase (GAPDH) from the extreme thermophile Thermus aquaticus has been solved at 2.5 Angstroms resolution. To study the determinants of thermostability, we compare our structure to four other GAPDHs. Salt links, hydrogen bonds, buried surface area, packing density, surface to volume ratio, and stabilization of alpha-helices and beta-turns are analyzed. We find a strong correlation between thermostability and the number of hydrogen bonds between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
137
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(149 citation statements)
references
References 53 publications
9
137
1
Order By: Relevance
“…This suggests that these two kinds of contacts may be also important to the thermostability of proteins. This is confirmed to the conclusions of Tanner et al 43 They studied the determinants of thermostability for GAPDH in the extreme thermophile Thermus aquaticus, and found that the number of hydrogen bonds between charged side chains and neutral partners can greatly enhanced the thermostability of proteins. An exception is the thermophilic protein (1xyz) in the 10th family.…”
supporting
confidence: 88%
“…This suggests that these two kinds of contacts may be also important to the thermostability of proteins. This is confirmed to the conclusions of Tanner et al 43 They studied the determinants of thermostability for GAPDH in the extreme thermophile Thermus aquaticus, and found that the number of hydrogen bonds between charged side chains and neutral partners can greatly enhanced the thermostability of proteins. An exception is the thermophilic protein (1xyz) in the 10th family.…”
supporting
confidence: 88%
“…The higher average B factor for the coenzyme-binding domain as compared with that of the catalytic domain has been observed previously (Tanner et al, 1996), and this structure shows more obvious differences of the B factors between the two domains. The B factors averaged over the main chain for the two subunits are plotted in Fig.…”
Section: Model Qualitysupporting
confidence: 75%
“…GAPDH structures were ®rst determined for the enzymes from lobster (Homarus americanus) muscle, and then for that from the moderate thermophile Bacillus stearothermophilus in several conformational states (Moras et al, 1975;Murthy et al, 1980;Skarzynski et al, 1987;Skarzynski & Wonacott, 1988). In addition, there are several crystallographic investigations for enzymes from other species such as human muscle (Mercer et al, 1976), Bacillus coagulans (Grif®th et al, 1983), Trypanosoma brucei (Vellieux et al, 1993), Thermotoga maritima (Korndorfer et al, 1995), Thermus aquaticus (Tanner et al, 1996), and E. coli (Due  e et al, 1996). These structural investigations provide important information on the folding, catalysis, allosterism mechanism, as well as the thermal stability of this important enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent analysis of the crystal structure of D-glyceraldehyde-3-phosphate dehydrogenase isolated from psychrophiles, mesophiles and thermophiles, the enzyme from the lobster Homarus americanus (which lives at 20°C ) was used as the psychrophilic reference [20]. Although the conclusions of this interesting work are not affected by such a taxonomical error, it is important to reconsider the definition of psychrophily in order to avoid future confusion.…”
Section: Psychrophily: An Evolving Conceptmentioning
confidence: 99%